The largest international digital logistics platforms: comparative analysis - S. E. Barykin; Yu. B. Egereva; E. V. Korchagina; O. V. Kalinina; E. S. Fedorova (Омский научный вестник: Серия "Общество. История. Современность")
Taking these prospects into account, the integration potential of Russia in the conditions of gradual trade and economic unity of the ASEAN countries can be considered in the aspect of formation of new strategic opportunities for interaction with the integration environment of Eurasia on the basis of investments in infrastructure development within the framework of the Eurasian Economic Union (EAEU). The advantages and disadvantages of the digital platforms and the characteristic features of international DLPs are highlighted. Based on the analysis, the necessity of developing an international digital platform in the EAEU is justified in the context of the development of international digital logistics platforms within the framework of the Eurasian Economic Union.